Design of a novel geothermal heating and cooling system: Energy and economic analysis. (15th January 2016) - Angrisani, G.; Diglio, G.; Sasso, M.; Calise, F.; Dentice d'Accadia, M.
Highlights: A desiccant-based air handling unit is coupled with a geothermal source. A TRNSYS model is developed to simulate both winter and summer period. Sensitivity analysis is carried out in order to evaluate the effects of the design parameters. Pay back period about 1.2 years and Primary Energy Savings higher than 90% were founded. Economic and energetic performance increase with to the use of Domestic Hot Water. Abstract: A dynamic simulation study in TRNSYS environment has been carried out to evaluate energy and economic performance of a novel heating and cooling system based on the coupling between a low or medium-enthalpy geothermal source and an Air Handling Unit, including a Desiccant Wheel. During summer season, a Downhole Heat Exchanger supplies heat to regenerate the desiccant material, while a certain amount of geothermal fluid is continuously extracted by the well in order to maintain high operating temperatures. Simultaneously, the extracted geothermal fluid drives an absorption chiller, producing chilled water to the cooling coil of the Air Handling Unit. Conversely, during the winter season, geothermal energy is used to cover a certain amount of the space heating demand. In both summer and winter operation modes, a geothermal energy is also used to supply Domestic Hot Water. A case study was analyzed, in which an existing low-enthalpy geothermal well (96 °C), located in Ischia (an island close to Naples, Southern Italy), is used to drive the geothermal system. Results showed that the performance of the proposed system is significantly affected by the utilization factor of Domestic Hot Water. In fact, considering a range of variation of such parameter between 5% and 100%, Primary Energy Saving increase from 77% to 95% and Pay-Back Period decreases from 14 years to 1.2 years, respectively. The simulations proved the technical and economic viability of the proposed system. In fact, a comparison with similar systems available in literature pointed out that the layout proposed in this work is characterized by better energy and economic performance, especially in the best scenario. Finally, a sensitivity analysis showed that the system performance is mainly affected by the nominal geothermal flow rate and by natural gas cost.